Business Strategies for Enhancing Competitive Advantage of Maritime Freight Forwarding Agents in Thailand - Trirananon, Kanjana; Sangvornyothin, Chantana (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
This article aimed to: 1) examine the level of strategic factors; 2) test the goodness-of-fit of the structural equation model; 3) investigate the influence of these factors on competitive advantage; and 4) formulate business strategies for freight forwarding agents in Thailand. This study employed a mixed-methods research design based on the concepts of marketing strategy, environmental turbulence, market orientation, and service quality. The research area focused on freight forwarding agent businesses in Thailand. The quantitative sample consisted of 420 entrepreneurs selected through quota sampling, while qualitative data were obtained from 10 experts. Data were collected using questionnaires and in-depth interviews. Quantitative data were analyzed using descriptive statistics and Structural Equation Modeling (SEM), while qualitative data were analyzed through content analysis. 1) The results indicated that marketing strategy, environmental turbulence, market orientation, and service quality were at a high level. 2) The structural equation model showed a good fit with the empirical data. 3) Marketing strategy and service quality had significant positive direct effects on competitive advantage, with the model explaining 87.70% of the variance. Service quality was found to have the strongest influence. 4) The findings led to the development of the PRIDER Model, which consists of six strategic components: People Integration, Reliability & Service Quality, Insight-driven Customer Focus, Differentiated Value-based Marketing, Efficient Cost Management, and Risk Management. The study contributes a strategic framework, the PRIDER Model, which can be applied to enhance competitive advantage and support sustainable development in the maritime logistics industry.